2017
DOI: 10.1371/journal.pone.0169728
|View full text |Cite
|
Sign up to set email alerts
|

Recreational Physical Activity and Premenstrual Syndrome in Young Adult Women: A Cross-Sectional Study

Abstract: IntroductionIt is estimated that up to 75% of premenopausal women experience at least one premenstrual symptom and 8–20% meet clinical criteria for premenstrual syndrome. Premenstrual syndrome substantially reduces quality of life for many women of reproductive age, with pharmaceutical treatments having limited efficacy and substantial side effects. Physical activity has been recommended as a method of reducing menstrual symptom severity. However, this recommendation is based on relatively little evidence, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
6
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 39 publications
3
31
6
10
Order By: Relevance
“…Dysmenorrhoea had been consistently associated with PMS and PMDD in several studies including ours 7,8,10,17,18 . Though many societies have recommended physical activity in the management of PMS, several studies including the present study had not found a correlation between physical activity and PMS 8,11,17,19 . Daley et al concluded that to make any evidence-based policy recommendation regarding the effectiveness of exercise, more high-quality research is required 20 .…”
Section: Discussioncontrasting
confidence: 76%
“…Dysmenorrhoea had been consistently associated with PMS and PMDD in several studies including ours 7,8,10,17,18 . Though many societies have recommended physical activity in the management of PMS, several studies including the present study had not found a correlation between physical activity and PMS 8,11,17,19 . Daley et al concluded that to make any evidence-based policy recommendation regarding the effectiveness of exercise, more high-quality research is required 20 .…”
Section: Discussioncontrasting
confidence: 76%
“…They include dietary recommendations [1], regular exercise [17], stress reduction skills training [18], and relaxation therapies [19]. Little evidence, however, supports the efficacy of these approaches as stand-alone treatments [20]. …”
Section: Introductionmentioning
confidence: 99%
“…Premenstrual syndrome (PMS) is a syndrome present during the luteal phase of the menstrual cycle and subsides at the time of menstrual bleeding, and it is characterized by psychological and physical symptoms, such as breast hypersensitivity, oedema, irritability, and depressed mood [35][36][37][38][39]. Our research demonstrates that the prevalence of PMS was significantly higher in the PG group.…”
Section: Discussionmentioning
confidence: 93%